Competentes! una visión para el desarollo de software - Bolaños Castro, Sandro Javier (Ingeniería, 1999)
Software development is one of the more complex problems by the high level of engineering that it must have. In this moment there are many tendencies and philosophies that introduce forms of conceiving and solving this problem, to generate a software product. Inside this tendencies exist the software conception like a component. This philosophy is accepted by its interesting characteristics and because it must be a good technique solution to the problem. This paper explain three technologies based on components: COM, JavaBeans and CORBA, their characteristics, fundamental guidelines and finally a vision criticizes.